Pengembangan Media Permainan Sirep berbasis Deduksi Sosial sebagai Sarana Sex Education dalam Pencegahan Pernikahan Dini pada Remaja di SMA Islam Karangploso - Salsabila, Sabrina Choirunisya; Mansur, Herawati (SENTRI: Jurnal Riset Ilmiah, 2026)
Early marriage remains an issue that requires serious attention because it may lead to various adverse impacts on adolescents' reproductive health, particularly among females. The lack of comprehensive sex education has resulted in adolescents having limited knowledge regarding reproductive health and the risks associated with early marriage. This study aimed to develop the SIREP social deduction-based game as a sex education medium for adolescents. The study employed a Research and Development (R&D) method. The research subjects consisted of 10 adolescents from SMA Islam Karangploso who participated in the product trial. The research instruments included a needs assessment questionnaire for adolescents, material expert validation sheets, media expert validation sheets, and a user response questionnaire. The developed SIREP game media covers topics on sexual behavior and its consequences, reproductive rights and health, sexual violence and harassment, and the impacts of early marriage. The findings showed that the SIREP game media achieved a feasibility score of 95.8% from the material expert, 97.5% from the media expert, and 90.5% from the respondents. Based on these results, the SIREP game media was categorized as highly feasible. The high feasibility scores indicate that the developed media is appropriate in terms of content, design, and ease of use as an educational tool for adolescents. Therefore, the SIREP social deduction-based game has the potential to serve as an alternative reproductive health education medium that is feasible, engaging, and acceptable to adolescents in delivering information on reproductive health and the prevention of early marriage.